2019
DOI: 10.1084/jem.20180649
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IL-10 signaling in macrophages limits bacterial killing driven by prostaglandin E2

Abstract: Loss of IL-10 signaling in macrophages (Mφs) leads to inflammatory bowel disease (IBD). Induced pluripotent stem cells (iPSCs) were generated from an infantile-onset IBD patient lacking a functional IL10RB gene. Mφs differentiated from IL-10RB−/− iPSCs lacked IL-10RB mRNA expression, were unable to phosphorylate STAT3, and failed to reduce LPS induced inflammatory cytokines in the presence of exogenous IL-10. IL-10RB−/− Mφs exhibited a striking defect in their ability to kill Salmonella enterica serovar Typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 119 publications
0
56
0
Order By: Relevance
“…However, in case of bacterial infection, these mechanisms that are beneficial under physiological conditions may limit the ability of the corneal ResMϕ to initiate a swift and sufficient innate immune/inflammatory response to bacterial infection. Inactivation of miR-183/96/182 releases its inhibition on IL-17f and IL-10 expression to enhance phagocytosis ( 63 – 66 ) and bacterial clearance capacity ( 58 60 , 65 , 66 ) of corneal ResMϕ and allow corneal ResMϕ to orchestrate an enhanced antibacterial inflammation and simultaneously help protect the integrity of the cornea and keeping the inflammatory response in check in early stages of P. aeruginosa infection. These effects may have contributed to the overall decreased severity of P. aeruginosa keratitis in the ko mice that we reported previously ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in case of bacterial infection, these mechanisms that are beneficial under physiological conditions may limit the ability of the corneal ResMϕ to initiate a swift and sufficient innate immune/inflammatory response to bacterial infection. Inactivation of miR-183/96/182 releases its inhibition on IL-17f and IL-10 expression to enhance phagocytosis ( 63 – 66 ) and bacterial clearance capacity ( 58 60 , 65 , 66 ) of corneal ResMϕ and allow corneal ResMϕ to orchestrate an enhanced antibacterial inflammation and simultaneously help protect the integrity of the cornea and keeping the inflammatory response in check in early stages of P. aeruginosa infection. These effects may have contributed to the overall decreased severity of P. aeruginosa keratitis in the ko mice that we reported previously ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In those patients inflammation is present despite transcription of IL-10 (patients express large amount of IL-10) and absence of pathogenic variants within the IL-10 receptor (exome sequencing did not reveal Mendelian forms of IL-10 receptor signalling defects in this cohort 30 ). The high expression of PTGS2 in this subgroup of patients with IBD represents an additional indicator for deregulated IL-10 responses and intestinal antimicrobial immunity 31 . Our experiments suggest that direct contact of monocytes with whole bacteria can induce IL-10 resistance that allows co-expression of IL-23 and IL-1 explain the signature of IL-10 non-responsiveness in a subgroup of patients with intestinal ulceration.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on samples from patients with IBD showed that inflammatory monocytes in a state of IL-10 non-responsiveness produce high levels of IL-23 ( 68 ). Although those patients express high levels of IL-10, the inflammation is still present due to dysregulated IL-10 responses and intestinal antimicrobial immunity ( 69 , 70 ). Therefore, the investigation of IL-23 signaling pathway in models of bacterial-induced intestinal inflammation with blocked IL-10R signaling can provide insights to understanding the immune regulations in the gut of IBD patients with dysregulated IL-10 responses.…”
Section: Discussionmentioning
confidence: 99%